Clinical Associations of Thyroid Hormone Levels with the Risk of Atherosclerosis in Euthyroid Type 2 Diabetic Patients in Central China - Limin Wang; Tingting Chen; Jiawei Yu; Huijuan Yuan; Xinru Deng; Zhigang Zhao (International Journal of Endocrinology)
Background. Thyroid function is associated with the etiology and pathogenesis of type 2 diabetes (T2D) and potentially contributes to the development of the complications of T2D. The association of thyroid hormones with atherosclerosis in euthyroid T2D patients is not clear. Purpose. To investigate the association of thyroid hormone levels with the risk of developing atherosclerosis in euthyroid T2D patients in Central China. Methods. This cross-sectional study recruited 910 euthyroid T2D patients from Henan Provincial People’s Hospital, China. Association among hemoglobin A1c (HbA1c), thyroid hormones, and the prevalence of atherosclerosis was assessed by multivariable Cox models after adjusting for covariates including age, BMI, duration of T2D, smoking status, SBP, TC, family history of T2D, and medications on hyperlipidemia. Results. Among all 910 subjects, 373 were diagnosed with atherosclerosis. There were 523 females and 387 males included in this study. The mean age was 51.9 years. The average BMI was 25.3 kg/m2. Low-normal serum-free triiodothyronine (FT3) levels (3.50–4.17 pmol/L) were associated with a high prevalence of atherosclerosis. Comparing with low-normal FT3, the prevalence ratio in patients with mid- (4.17–4.83 pmol/L) and high-normal FT3 level (4.83–6.50 pmol/L) is 0.74 (95% CI 0.56 to 0.97, p=0.029) and 0.63 (95% CI 0.46 to 0.87, p=0.005) after adjusting for covariates. High level of free thyroxine (FT4) also had decreased risk for atherosclerosis. Thyroid-stimulating hormone (TSH) and FT3 to FT4 ratio did not show significant association with the development of atherosclerosis. Conclusion. T2D patients with low but clinically normal FT3 level are more likely to develop macrovascular complications comparing with those with mid- and high-normal FT3 level.